Prevalence and antimicrobial susceptibility of Mycoplasma gallisepticum and Mycoplasma synoviae isolated from the central peninsular Malaysia - Ahmad Rufai, Attahiru; Zakaria, Zunita; Yu, Choo Yee; Ganapathy, Kannan; Abu, Jalila; Ahmad, Nur Indah; Tee, Chin Tat (Elsevier, 2025)
Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) have been recognized and listed by the World Organization for Animal Health (WOAH) as the two most pathogenic avian mycoplasma species. These organisms can cause a wide range of symptoms in birds, including acute and chronic respiratory diseases, synovitis, air sacculitis, severe weight loss, eggshell abnormalities, and reduced egg production. In Malaysia, previous studies have mainly focused on seroprevalence, and prevalence based on polymerase chain reaction (PCR) with molecular characterization, which have confirmed the presence of MG and MS among the poultry population. These could pose significant economic challenges for farmers. To investigate this further, the present study was conducted to determine the prevalence and the antimicrobial minimum inhibitory concentrations (MIC) of MG and MS isolates that are circulating in the farms in central region of Peninsular Malaysia. A total of 407 choanal cleft swab samples were collected from various poultry farms in the central Peninsular and were subjected to isolation and PCR. Of these, 103 (25.3 %) MG, 173 (42.5 %) MS and 36 (8.8 %) MG-MS were obtained by PCR, while 61 (15.%) 14(3.4 %) and 1 (0.2 %) successful isolation of MG, MS, and MG-MS were made respectively. Antimicrobial susceptibility testing showed that MG and MS isolates had reduced susceptibility to lincomycin (4 - ≥ 32 µg/mL) and erythromycin (≤0.12 - ≥ 64 µg/mL) respectively, while Tylvalosin (≤0.015 – 0.5 µg/mL), Tiamulin (≤0.015 – 0.25 µg/mL) and Doxyccline (0.06 -0.5 µg/mL) showed the highest susceptibility for these organisms. These findings highlights that while the threat of MG and MS infections persist, special attention should be directed towards the growing prevalence of MS. Furthermore, regular monitoring of antimicrobial susceptibility profiles should guide treatment strategies and address potential concerns regarding antimicrobial resistance.